Analisis Faktor Risiko Kejadian Pneumonia Komunitas di Rumah Sakit Umum Daerah Kabupaten Buton Selata - Kolewora, Yusuf Musafir; Adeningsi. M, Arta Sri; Widjaya, Mario Polo (LPPM Institut Pendidikan Nusantara Global, 2025)
Pneumonia is an acute inflammation of the lung parenchym caused by pathogenic infection (bacteria, viruses, fungi and parasites) but not including Mycobacterium tuberculosis. Based on clinical and epidemiological aspects, pneumonia is divided into communnity-acquired pneumonia, hospital-acquired pneumonia, and ventilator-associated pneumonia. It has been reported that there has been an increase in pneumonia cases in South Buton Regency. This study is to determine the risk factors incidence for community-acquired pneumonia at South Buton District General Hospital. This study used an observational analytical method with a case control study design with data collection from patient medical records at the South Buton District General Hospital in 2022-2024. The sampling technique used total sampling technique in case samples and purposive sampling in the control group. The case group was patients diagnosed with community-acquired pneumonia and the control group was patients not diagnosed with community-acquired pneumonia. Data analysis was carried out the chi-square statistical test, then continued by determining the Odds Ratio (OR). The results of the study show that age (p= 1,000 ; OR: 1,000; 95% CI: 0,516-1,937), gender (p = 1,000 ; OR: 1,000; 95% CI: 0,502-1,991), nutritional status (p = 0,312 ; OR: 1,490; 95% CI: 0,767-2,893), smoking (p = 0,012 ; OR: 2,503; 95% CI: 1,274-4,917), and comorbidity(p = 0,040 ; OR: 2,165; 95% CI: 1,091-4,296). Age and gender are not risk factors. Whereas nutritional status, smoking and comorbidity are risk factors for community-acquired pneumonia at South Buton District General Hospital.